The 1st IMAS International Conference On Multidisciplinary Academic Studies Abstract Book - Mihaela POP; Alice-Dalina MATEI-CERNĂIANU (Kürşat Çapraz, 2023)
The 1st IMAS International Conference Abstract Book.